Musik Ritual Bebalai dalam Upacara Adat Pesta Laut Bontang Kuala di Bontang Kalimantan Timur - Hirda Yulinalmi; Asril Gunawan; Zamrud Whidas Pratama (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This research aims to describe the presentation form and function of Bebalai music in the traditional ceremony of